On-chip analysis of atmospheric ice-nucleating particles in continuous flow. Issue 16 (14th July 2020) - Tarn, Mark D.; Sikora, Sebastien N. F.; Porter, Grace C. E.; Wyld, Bethany V.; Alayof, Matan; Reicher, Naama; Harrison, Alexander D.; Rudich, Yinon; Shim, Jung-uk; Murray, Benjamin J.
Abstract : A microfluidic platform for the analysis of atmospheric ice-nucleating particles (INPs) via the freezing of thousands of droplets in continuous flow. Abstract : Ice-nucleating particles (INPs) are of atmospheric importance because they catalyse the freezing of supercooled cloud droplets, strongly affecting the lifetime and radiative properties of clouds. There is a need to improve our knowledge of the global distribution of INPs, their seasonal cycles and long-term trends, but our capability to make these measurements is limited. Atmospheric INP concentrations are often determined using assays involving arrays of droplets on a cold stage, but such assays are frequently limited by the number of droplets that can be analysed per experiment, often involve manual processing ( e.g. pipetting of droplets), and can be susceptible to contamination. Here, we present a microfluidic platform, the LOC-NIPI (Lab-on-a-Chip Nucleation by Immersed Particle Instrument), for the generation of water-in-oil droplets and their freezing in continuous flow as they pass over a cold plate for atmospheric INP analysis. LOC-NIPI allows the user to define the number of droplets analysed by simply running the platform for as long as required. The use of small (∼100 μm diameter) droplets minimises the probability of contamination in any one droplet and therefore allows supercooling all the way down to homogeneous freezing (around −36 °C), while a temperature probe in a proxy channel provides an accurate measure of temperature without the need for temperature modelling. The platform was validated using samples of pollen extract and Snomax®, with hundreds of droplets analysed per temperature step and thousands of droplets being measured per experiment. Homogeneous freezing of purified water was studied using >10 000 droplets with temperature increments of 0.1 °C. The results were reproducible, independent of flow rate in the ranges tested, and the data compared well to conventional instrumentation and literature data. The LOC-NIPI was further benchmarked in a field campaign in the Eastern Mediterranean against other well-characterised instrumentation. The continuous flow nature of the system provides a route, with future development, to the automated monitoring of atmospheric INP at field sites around the globe.